KONSTRUKSI FEMININITAS DALAM CERITA PENDEK â€œFATAMORGANAâ€ KARYA AAM AMILIA - Rani, Seni Melia; Priyatna, Aquarini; Muhtadin, Teddi (HUMANIKA, 2017)
The thesis aims to describe the construction of femininity in Aam Amiliaâ€™s short story entitled â€œFatamorganaâ€. Aam Amilia is the most productive woman author in Sundanese literature. In this short story, Aam shows the construction of femininity of Sundanese woman through the relationship between men and women in everyday life, especially in marriage. The short story â€œFatamorganaâ€ shows two characters of Sundanese women tend to be contradictory, that is the women that stay at home as housewives and women that have full time career outside. It is through the narrative and vocalization in short story thatboth of the figures are appearead to have different opinions in defining the position of mother. Nevertheless, this short story takes side to ideal femininity that is concieved from men assumptions.